UJI BAKTERIOLOGIS DAGING SEGAR PENSI (Corbicula sumatrana Clessin) YANG BERASAL DARI DANAU SINGKARAK - Misnawati, Misnawati; Indriati, Gustina; Zeswita, Armein Lusi (Pendidikan Biologi, 2013)
ABSTRACTÂ Corbicula sumatrana Clessin is typical of freshwater mussels or brackish water economically valuable. C. sumatrana Clessin a shellfish known people with the name pensi. Pensi consumed by people as a source of animal protein and animal feed ingredients. Singkarak Lake used by people in daily life from the source of drinking water, toilets, fisheries, irrigation, PLTA and Tourism. The many activities of the community could be expected to cause pollution and affect the C. sumatrana Clessin. Shellfish become vectors of biotoksin because his diet filter-feeder. Pensi meat is an excellent medium for bacterial growth. This study aims to determine the presence of Escherichia coli and Salmonella sp. on fresh meat Pensi (C. sumatrana Clessin) originating from Singkarak Lake. The research was conducted in July - August 2013. This research is a descriptive method, by looking at and analyzing the presence of microorganisms are bacteria E. coli and Salmonella sp. The method used to determine the bacteriological quality of the meat is pensi by MPN method and examination of Salmonella. Data were analyzed by calculating the number of bacteria E. coli by observing the number of positive results of the estimation of presumptive test, confirmative test and completed test. The next number of bacteria from each positive results are matched with MPN table. Test Salmonella sp. done by looking at the colony grows. Results of bacteriological tests on meat samples were examined in Microbiology Laboratory Research and Industry Standards (BARISTAND Industry) Padang showed that of the four samples tested, three of which were positive for the bacteria E. coli samples take in Nagari Tikalak, Nagari Singkarak, Nagari Saning Bakar and all samples contained Salmonella sp. Of this study is suggested to consumers that cooking pensi perfectly, to avoid diseases that may occur because it is caused by bacteria.Â Â